Journalism in times of post-truth and misinformation. : Analizing the work of digital platform’s journalists from El Comercio and RPP - Espinoza Guanilo, Antonio Hector (2024)
In the face of the digital and communications revolution, journalism has reached new platforms on the Internet where it often seeks to reinvent itself to face the new information ecosystem. This research aims to know about the journalistic work, through internet, in contrast with one of the major issues of our time: the post-truth and misinformation. The data was collected from journalists who work in El Comercio and RPP, two of the most important media in Peru, following qualitative methods and in-depht interviews. The results obtained shows ethics and journalistic values, more than ever, are very important to deal with the new information ecosystem and its threats. In addition, online content speed and variety, and the different sources where it comes from, despite the journalists’ effort, present a risk to publish and consume information nowadays.